Residuos vegetales de Banano (Musa x paradisiaca L), coco (Cocos nucifera L) y caña de azúcar (Saccharum officinarum L) para la obtención de fibras textiles - Montoya Murillo, Lorenzo (2024)
Textile fibers of vegetable origin from residues comprise an immense amount of material resulting from harvesting or industrialization operations; these residues can act as a substitute for synthetic fibers of petrochemical origin, which generate contamination of watersheds and greenhouse gas emissions, in addition to their slow degradation. In this study, banana (Musa x paradisiaca L), coconut (Cocos nucifera L) and sugar cane (Saccharum officinarum L) residues are analyzed to obtain textile fibers, resulting that at concentrations lower than 10 % NaOH the qualities of the fibers are improved, while the best lignocellulosic material to obtain cellulose and later manufacture rayon yarn is the banana rachis. In turn, the most versatile fibers for the manufacture of accessories is bagasse, given the balance between its performance in obtaining, mechanical strength and modulus of elasticity, the latter two being conferred by its amount of cellulose, fiber diameter and MFA (microfibrillar angle), while coconut fibers are distinguished mainly for applications in outdoor environments for its resistance capacity conferred by its composition.